Mensuração de eficiência no setor público: estudo de caso sobre o processo de gestão orçamentária do ministério da educação - Lima, Cristian de Oliveira (2015)
The need for pursuing efficiency is of great relevance, whichever the model of public administration adopted. Despite the popularity of the concept, its measuring is an extremely complex issue, especially in the public sector. Some authors consider the lack of objective indicators for its evaluation an important obstacle in implementing managerial reforms. The solution seems to be measuring costs, specifically by the activity-based costing methodology. The present work had the objective of applying this methodology to a case study: evaluate the impact in terms of technical efficiency caused by the changes in the budget management process of the Ministry of Education. The resulting quantitative indicators are expressive considering the increase in efficiency and timeliness when introducing information and communication technology tools in the analyzed process, but, at the same time, highlight the need for structural changes (in legislation, forms of control, etc.). It is understood that the work may yet contribute in order for the changes discussed in the case study be adopted by the remaining federal public organs, as well as for the consolidation and diffusion of the methodology as an important tool in the evaluation of process changes.